Prediction Of The Stable Genotypes Based On Analysis Of Genotype × Environment Interaction In Soybean (Glycine Max (L.) Merrill) (International Journal of Food and Nutritional Sciences, 2021)
Soybean plays a major role in the world food systems. Soybeans are legumes that are grown for oil and protein around the world. Indian agriculture is studded with several landmarks. The “yellow revolution” is one of them, associated with increased oilseed production and soybean has significant contribution in this The present experiment was carried out for estimation of the stability of twenty elite soybean genotypes under varying environmental conditions for grain yield and yield contributing characters. The field experiment was laid down in randomized complete block design with three replications at four different locations (Norman E. Borlaug Crop Research Centre at G. B. Pant University of Agriculture and Technology, Pantnagar, ARS, Majhera, IARI, New Delhi and BAU, Kanke, Ranchi) during Kharif 2010 and Kharif2011.